Pedagogical Strategy of Writing Paragraph Using Edmodo to Enhance Writing Skill for EFL Students - Duwila, Shanty AYPS; Khusaini, Taufik (English Education Department STKIP Al Hikmah Surabaya, 2019)
In today's digital era, there are a number of social media that can be used as a tool to help writing skills for those who learn English. One of the media is